Bahasa Ngapak sebagai Atribut Wong Banyumasan - Amad Wahyu Rusli Sofiyulloh (Journal on Education, 2024)
Wong Banyumasan is a community that lives in the Banyumas Residency. Wong Banyumasan has a blakasuta character. Besides blakasuta, there are other terms such as cablaka and thokmelong. In their life, wong Banyumasan use ngapak language as their daily language. Ngapak language is the oldest language among other Javanese languages. In this case, as the oldest language, ngapak language has differences with other Javanese languages. In addition, ngapak language is the biggest attribute of the wong Banyumasan. This is because ngapak language is used as the mother tongue by the wong Banyumasan and ngapak language only exists in the Banyumas Residency. With this statement, this paper analyses ngapak language as an attribute of wong Banyumasan. This research uses methods used in historical research methods, namely heuristics, verification, interpretation, and historiography. In addition, the data and topics studied in this paper show that this paper is the result of qualitative research. The formulation of the problem studied in this research is what is meant by wong Banyumasan, how the existence of ngapak language in the development of won Banyumasan lives, and why ngapak language is an attribute of wong Banyumasan